The Effect Of Traditional Lampung Music Therapy On Pain Response In Postoperative Patients At Airan Raya Hospital In Lampung - Emilia Septianti (International Journal of Health Engineering and Technology, 2026)
Surgical procedures cause pain, as an unpleasant emotional and sensory experience caused by tissue damage. Traditional Lampung music therapy is a non-pharmacological strategy with the advantage that when the patient reaches full relaxation the perception of pain is reduced, so traditional music therapy (distraction) is very effective when used to treat pain in post-operative patients. The research aims to determine the effect of traditional Lampung music therapy on pain intensity in post-mammary ca surgery patients. This one group pre post test research design was without a comparison group (control) with a sample of 18 respondents. Data on the pain scale felt by respondents before being given traditional Lampung music therapy was moderate pain scale for 15 respondents (83.3%), severe pain scale for 3 respondents (16.7%). After being given treatment, the pain intensity became mild pain scale for 11 respondents (61.1%) and moderate pain scale for 7 respondents (38.9%). The conclusion is that there is a significant influence between traditional Lampung music therapy on pain intensity in post-mammary ca surgery patients, p value = 0.000. Patients can independently use this technique at home to reduce pain after surgery.